Bilateral inflammatory myofibroblastic tumor mastoiditis. Issue 11 (26th June 2015) - Rodgers, Brian; Bhalla, Vidur; Zhang, Da; El Atrouni, Wissam; Wang, Fen; Sundararajan, Jayashree; Lin, James; Irish, Jonathan
Abstract Background Inflammatory myoblastic tumors (IMTs) are rare, mesenchymal neoplasms most commonly located in areas of previous inflammation. In the temporal bone, these tumors typically present as solitary, space‐occupying lesions that clinically resemble chronic otitis media. Methods We present a case of bilateral IMTs with facial nerve involvement, sigmoid sinus thrombosis, leptomeningeal enhancement, and seizures. Results/Conclusion This case demonstrates the need for a high index of suspicion of IMT when imaging reveals bilateral mastoid opacification. These tumors are more aggressive than their orbital counterparts and require multimodality therapy to prevent recurrence and alleviate severe neurotologic symptoms. © 2015 Wiley Periodicals, Inc. Head Neck 37: E142–E145, 2015